The Impact of Teacher Support in Improving Students' Religious Attitudes Through the Learning Process: Case Study in Junior High School, Malang City - Muhammad Hilal Maulidi; Muhammad Adip Fanani; Rahmat Aziz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In social life, whether in the home or school environment, there is a need to instill religiosity which is useful for human life. With this cultivation, humans know that they have God who owns everything, thus reminding us as humans not to be proud of what we already have and to carry out all His commands and stay away from His prohibitions. In the school environment, this is also important to instill so that students know the benefits of instilling an attitude of religiosity. The aim of this research was to determine the effect of class activities on junior high school students' religious beliefs. The research method used was quantitative using a descriptive approach. This approach starts from a theoretical framework, expert ideas, or understanding that is returned to several problems in order to obtain justification through data according to experience in the field. With a population of 255 junior high school students in Malang City, data was collected through observation and questionnaires regarding class activities and student religiosity. The results of the regression analysis of the class activity variable influence student religiosity with a significance value of 0.00 < 0.005. The classroom activity variable has six indicators, namely: classroom rules, student support, student involvement, positive teaching, encouragement and classroom management. Of these six indicators, the one that has the most influence on participants' religious beliefs is teacher support with a significance value of 0.07 < 0.005. This research has an impact on Student Religiosity by 44%.